2021
DOI: 10.1111/ecc.13402
|View full text |Cite
|
Sign up to set email alerts
|

Occupational rehabilitation of male breast cancer patients: Return patterns, motives, experiences, and implications—A qualitative study

Abstract: While breast cancer is the most common cancer among women (Bray et al., 2018), it is considered a rare disease among men as only 1% of patients are male (Giordano, 2018). This inequality in prevalence exposes male breast cancer patients (MBCPs) to particular disadvantages such as diagnosis delays, treatment deficits, and stigmatisation due to the perception of breast cancer as a 'women's disease' (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
17
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 38 publications
2
17
0
6
Order By: Relevance
“…5,18,19 Survivors may work because they need to (eg, insurance, income), but they may also work because they want to (eg, for a sense of normalcy and personal identity, distraction, need for activity, social contacts). 20,21 Approximately 35% to 46% of people diagnosed with cancer in the United States are between the ages of 20 and 64 years, and thus are generally considered to be of working age. 1,3,22 Therefore, as many as 6 to 8 million cancer survivors in the United States are at risk for difficulties surrounding employment.…”
Section: Working and Returning To Work After A Cancer Diagnosismentioning
confidence: 99%
“…5,18,19 Survivors may work because they need to (eg, insurance, income), but they may also work because they want to (eg, for a sense of normalcy and personal identity, distraction, need for activity, social contacts). 20,21 Approximately 35% to 46% of people diagnosed with cancer in the United States are between the ages of 20 and 64 years, and thus are generally considered to be of working age. 1,3,22 Therefore, as many as 6 to 8 million cancer survivors in the United States are at risk for difficulties surrounding employment.…”
Section: Working and Returning To Work After A Cancer Diagnosismentioning
confidence: 99%
“…Our research showed that experiencing MBC is likely to be associated with health professionals' uncertainty and unmet needs (Halbach et al, 2020;Hiltrop et al, 2021;Midding et al, 2018Midding et al, , 2019. We thank the authors for the critical debate and appraisal of our study.…”
mentioning
confidence: 78%
“…gradual return) is valuable to design patient-centred, need-oriented interventions and that (gradual) RTW planning could be important for a successful RTW. Additionally, interventions targeting employers or caretakers could be beneficial when aiming for satisfying RTW outcomes due to specialists' lacking knowledge (Lamort-Bouché et al, 2020) and different communication needs of patients with the workplace (Hiltrop et al, 2021).…”
mentioning
confidence: 99%
“…While 70% of breast CSs who were employed at the time of diagnosis returned to work on average 8.3 years into survival, 3 problems meeting demands at work in the long run apparently exist. This aspect leads some researchers to understand return to work (RTW) as a process rather than a single event 4,5 …”
Section: Introductionmentioning
confidence: 99%